PATH INTEGRAL QUANTIZATION OF DISSIPATIVE SYSTEMS - Eyad H. Hasan; Ola A. Jarab'ah; Khaled I. Nawafleh (European Scientific Journal, ESJ, 2014)
This paper investigated the basic formalism for treating the dissipative Hamiltonian systems within the framework of the canonical method using the path integral quantization. The Hamiltonian treatment of the dissipative systems leads to obtain the equations of motion as a total differential equation in many variables which require the investigation of integrability conditions on the action and the equations of motion. In this formalism, the action integral for dissipative systems is obtained from equations of motion and written in phase space. Besides, the quantization of these systems is investigated using the action to construct the wave function in terms of the canonical phase space coordinates. Two examples are examined, the free particle and the simple harmonic oscillator.